2020
DOI: 10.1021/acsabm.0c00854
|View full text |Cite
|
Sign up to set email alerts
|

Nano- and Microfiber PVB Patches as Natural Oil Carriers for Atopic Skin Treatment

Abstract: Atopic dermatitis (eczema) is a widespread disorder, with researchers constantly looking for more efficacious treatments. Natural oils are reported to be an effective therapy for dry skin, and medical textiles can be used as an alternative or supporting therapy. In this study, fibrous membranes from poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) (PVB) with low and high molecular weights were manufactured to obtain nano- and micrometer fibers via electrospinning for the designed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…The designed patches consisting of the layered sPCL/pPCL fibers increased the hemp oil release on volunteers’ skin up to 55% within 6 h. In previous studies, the patches based on electrospun PVB fibers showed approx. 13% release of evening primrose oil within 1 h [ 24 ]. The prolonged-release carriers are in high demand in AD treatment, as the moisturization time is elongated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The designed patches consisting of the layered sPCL/pPCL fibers increased the hemp oil release on volunteers’ skin up to 55% within 6 h. In previous studies, the patches based on electrospun PVB fibers showed approx. 13% release of evening primrose oil within 1 h [ 24 ]. The prolonged-release carriers are in high demand in AD treatment, as the moisturization time is elongated.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the spreading and release of oil on PCL patches we used hemp seed oil with surface-free energy (SFE) of 31.7 ± 0.6 mN·m −1 and viscosity of 50.6 ± 0.2 MPa·s. The SFE and viscosity were measured, as previously reported [ 24 ]. PCL patches were placed onto the skin model, and the volume of 25 µL of hemp oil was deposited per sample, see Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The obtained diameter of PHBV fibers was close to the value of 2.79 ± 0.2 μm, as previously reported ( Kaniuk et al, 2020 ). The morphology and size of fibers prepared via electrospinning were affected by the polymer solution, environmental conditions, and applied electric field ( Krysiak et al, 2020 ; Szewczyk et al, 2020 ). It was followed by mechanical ( Ura et al, 2020 ) and surface properties ( Metwally et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…23,75 However, the size of the fibers in the mat is an important factor. 23,24,75 Electrospun PHBV fibers and polymer blend fibers with oil are characterized by an increase in the fiber diameter along with the amount of added oil. Therefore, the largest area of diffusion can be observed for pure PHBV fibers and a smaller area for oily fibers.…”
Section: Wettability -Water Contact Anglementioning
confidence: 99%